Structural Features of Nanocrystalline Magnetite Obtained by Different Syntheses According to X-Ray Diffraction and Electron Microscopy Data - A.N. Kalinkevich; O.V. Kalinkevich; A.S. Stanislavov; V.N. Kuznetsov; L.F. Sukhodub; K.V. Tyschenko; M.G. Demidenko; S.N. Danilchenko (Журнал нано- та електронної фізики)
Structural features of nanosized magnetite Fe3O4 synthesized in the presence of polymeric matrices (polysaccharide chitosan, etc.) were studied using transmission electron microscopy (TEM) and X-ray diffraction analysis. The data obtained strongly suggest the influence of the polysaccharide matrix on the magnetite nanoparticles growth inhibition and size stabilization. The controlled size decrease of Fe3O4 nanoparticles is accompanied with the increase of crystal lattice imperfection and the decrease of the unit cell size. The utility of TEM and XRD complementary use for the determination of nanosized magnetite particles structure and substructure parameters is shown in the present paper.